Telocytes express PDGFRα in the human gastrointestinal tract. Issue 9 (24th September 2013) - Vannucchi, Maria‐Giuliana; Traini, Chiara; Manetti, Mirko; Ibba‐Manneschi, Lidia; Faussone‐Pellegrini, Maria‐Simonetta
Abstract: Telocytes (TC), a cell population located in the connective tissue of many organs of humans and laboratory mammals, are characterized by a small cell body and extremely long and thin processes. Different TC subpopulations share unique ultrastructural features, but express different markers. In the gastrointestinal (GI) tract, cells with features of TC were seen to be CD34‐positive/c‐kit‐negative and several roles have been proposed for them. Other interstitial cell types with regulatory roles described in the gut are the c‐kit‐positive/CD34‐negative/platelet‐derived growth factor receptor α (PDGFRα)‐negative interstitial cells of Cajal (ICC) and the PDGFRα‐positive/c‐kit‐negative fibroblast‐like cells (FLC). As TC display the same features and locations of the PDGFRα‐positive cells, we investigated whether TC and PDGFRα‐positive cells could be the same cell type. PDGFRα/CD34, PDGFRα/c‐kit and CD34/c‐kit double immunolabelling was performed in full‐thickness specimens from human oesophagus, stomach and small and large intestines. All TC in the mucosa, submucosa and muscle coat were PDGFRα/CD34‐positive. TC formed a three‐dimensional network in the submucosa and in the interstitium between muscle layers, and an almost continuous layer at the submucosal borders of muscularis mucosae and circular muscle layer. Moreover, TC encircled muscle bundles, nerve structures, blood vessels, funds of gastric glands and intestinal crypts. Some TC were located within the muscle bundles, displaying the same location of ICC and running intermingled with them. ICC were c‐kit‐positive and CD34/PDGFRα‐negative. In conclusion, in the human GI tract the TC are PDGFRα‐positive and, therefore, might correspond to the FLC. We also hypothesize that in human gut, there are different TC subpopulations probably playing region‐specific roles.